Seasonal variation of plant mineral nutrition in fruit trees - Cruz, André Freire (2019)
This research evaluated the monthly variation of plant mineral nutrition in six species of fruit trees over a year. Leaf samples were taken from the fruit trees and nutritional status (N, P, K, Ca, Mg, Fe, Zn, Cu, Mn, and Mo) was determined in the leaves in a month basis from April until November for apple, persimmon and peach. Mandarin mineral nutrition was monitored for one year, and grape and fig from May to November. Using this data, the Diagnosis Recommendation Integrated System (DRIS) was also calculated to evaluate the nutrient balance in the plants. The concentration of N and P had seasonal differences, especially in apple and peach, which reached the peak during the summer. Apple, fig, and grape trees had large ranging on their mineral contents over the year, especially with the P and K levels reaching the minimum during the harvesting season. However, the seasonal changes in leaf micronutrient concentrations were not uniform and not affected by phenological stage. The DRIS data demonstrated that mandarin had the best nutrient balance compared to others and that K was the most limiting element among the fruit trees. In summary, the current data suggest the occurrence of a significant seasonality in mineral nutrition in these six fruit trees, especially in temperate ones.